A better link between security and development in the European Union? The European Community's Instrument for Stability (IfS) - Stefan Gänzle (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
Tackling the linkage between security and development policy poses policy challenges to many development actors – whether in the context of fragile states, natural disaster responses, or post-conflict reconstruction. The challenge is particularly pronounced for the European Union (EU), since policy issues are unlikely to respect any of the complex delimitations of competences within the EU. Europe's multilevel governance system involves a plethora of institutions and actors from both the European and Member State levels. These actors are constantly compelled to find new ways to increase nter-institutional as well as intra-institutional collaboration in order to provide effective policy responses to cope with these new challenges that evolve in a `grey area' – to be understood in the sense of overlaps – between traditional foreign, security and development policies. In 2007, the European Union launched an `Instrument for Stability' (IfS) which adds new capacities to the EU's crisis management toolbox: First, it enables the Community to quickly respond to political crises and natural disasters – and substantially increases its capacity for sustained funding from Community sources. Second, it provides a clearer picture of European Community (EC) and Union competence when it comes to emphasising the linkage between security and development policies. Third, it enables the EU to draw regional organisations and non-governmental organisations (NGOs) much closer towards implementation of EU policies.
Keywords: 330